Alienation and resistance in franz kafka's the metamorphosis - How, Mandy (2016)
My thesis examines Gregor Samsa's transformation as a symptom of human helpless and Marxist alienation, while simultaneously exploring his metamorphic form (in particular its elements of abjection and hybridity) as a possibility of freedom and resistance against the modern capitalist system. Subsequently, this essay investigates the extent of Gregor's deviation from the human society and the capitalist ideology, and concludes that Gregor and his family continue to be subjugated by the capitalist system.